Ameliorative effects of Sesamum Indicum aqueous extract on Letrozole-induced polycystic ovary syndrome in adult female rats and formulation of sesame syrup - Zeynab Khosrowpour; Shamim Sahranavard; Fatemeh Jafari; Mojgan Tansaz; Shirin Fahimi; Mehrdad Faizi (Journal of Traditional and Complementary Medicine, 2025)
Background: In this study, we explored the potential of Sesamum indicum L. aqueous extract (AES) in treating Polycystic ovary syndrome (PCOS) in female rats and developing a medicinal syrup from it. Experimental procedure: We conducted experiments on 42 adult Sprague Dawley female rats, dividing them into six groups. The control group received a 1% carboxymethyl cellulose vehicle, while the other groups were given letrozole orally for 21 days followed by administration of AES, metformin, and distilled water after 28 days of PCOS induction. Results: Results showed that after letrozole administration, PCOS was confirmed by irregular estrous cycles and increased LH and testosterone levels. The AES and metformin improved estrus cyclicity in rats compared to the PCOS group. Additionally, LH levels and LH/FSH ratio were significantly reduced in AES and metformin groups, while testosterone levels decreased and estradiol levels increased. Histological studies revealed normal follicular development in these groups with fewer cystic follicles. Conclusion: In conclusion, the AES showed promise in alleviating PCOS symptoms due to its phytochemical components such as β-sitosterol, campesterol, and stigmasterol, and sesquiterpenes with phytoestrogenic, androgenic and antiinflammatory effects. The 400 mg/kg dose was found to be the most effective in this experiment.